An evaluation of the St Christopher's Hospice rehabilitation gym circuits classes: Patient uptake, outcomes, and feedback. (December 2014) - Talbot Rice, Helena; Malcolm, Lorna; Norman, Kate; Jones, Alison; Lee, Katherine; Preston, Gail; McKenzie, David; Maddocks, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> Background Evidence suggests exercise may benefit patients with advanced progressive illness and some hospice day services now provide dedicated gym space. However, supporting data for such a service development are limited. We describe patient referrals, interventions, feedback, and potential impact of a nine-session, outpatient, hospice-based, circuit exercise programme. Methods Consecutive referrals to physiotherapy over a 6-month period commencing March 2013 were followed prospectively. Physical function (short physical performance battery (SPPB), grip strength), fatigue (Functional Assessment of Chronic Illness Therapy), psychological well-being (General Health Questionnaire), and patient satisfaction (FACIT-PS) were assessed pre- and post-programme. Results Of 212 referrals, 61 (29%) with a range of cancer and non-cancer diagnoses (median [inter-quartile range] survival 67 [50–137] days) were considered appropriate for the circuits of whom 54 (89%) started. There were no statistical differences between those completing and not-completing with regards to age, diagnosis, social status, or survival. In completers (n = 28), 4-m gait speed (mean Δ [95% confidence intervals] 0.23 [0.03, 0.44] m/seconds), five sit-to-stand time (mean Δ −5.44 [−10.43, −0.46] seconds) and overall SPPB score changed statistically, while grip strength did not (mean Δ 0.65 [−1.39, 2.96] kg). Psychological well-being, quality of life, and fatigue remained unchanged. Patients felt the physiotherapists gave clear explanations, understood their needs, and would recommend the service to others. Conclusion A hospice-based programme is one way to offer exercise to a range of patients with advanced progressive illness. Despite excellent feedback, only half of patients completed the nine-session programme in full and evidence of benefit was limited. Future work should explore the broader benefits of participation and whether delivering programmes or elements of them in shorter time frames is more beneficial.